Analisis Kesiapan Transformasi Digital UMKM dalam Penggunaan Aplikasi Pos Digital System dengan Metode I-Toe Framework - Yashinta Putri Dwi Astuti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
Information technology has an important role in the continuity of business activities for MSMEs. The application of technology to build a business is called effective and efficient digital transformation for MSMEs. One form of digital transformation is in the aspect of recording transactions and finances called Point of Sale (POS). POS is an application in the form of an online cashier with integrated electronic transaction service features which is aimed at increasing the sustainable development of digital entrepreneurs or Digipreneurs through digital transaction services to analyze administrative and financial matters which can help MSMEs. This research aims to prepare for the digital transformation of MSMEs in using digital POS system applications using the I-TOE framework. This research is qualitative in nature with data collection techniques by conducting interviews with 6 MSMEs in Salatiga, Central Java. From the interview results, it can be concluded that through the I-TOE framework, it is known that the readiness for digital MSME transformation is influenced by several aspects (1) Type of business, (2) Age of the manager. (3) Human resources and (4) Environmental demands.